A case-control study of urinary levels of iodine, perchlorate and thiocyanate and risk of papillary thyroid cancer. (November 2018) - Zhang, Lei; Fang, Congrong; Liu, Liping; Liu, Xin; Fan, Sai; Li, Jingguang; Zhao, Yunfeng; Ni, Song; Liu, Shaoyan; Wu, Yongning
Abstract: Background: The incidence of thyroid cancer has recently increased worldwide. With the exception of radiation exposure, the effects of potential risk factors on thyroid cancer incidence remain controversial. Objectives: The association between exposure to iodine, perchlorate, and thiocyanate and papillary thyroid cancer (PTC) incidence was evaluated and risk factors were predicted. Methods: A pair-matching case-control study was performed including 116 age- and sex-matched PTC cases and 116 non-PTC controls. Iodine, perchlorate, and thiocyanate concentrations in urine specimens were determined by inductively coupled plasma mass spectrometry and ultra-performance liquid chromatography–tandem mass spectrometry. The association between iodine, perchlorate, and thiocyanate urinary concentrations and PTC was evaluated using univariable conditional regression logistic analysis followed by multivariable conditional logistic regression analyses with backward stepwise selection to predict risk factors for PTC. Results: After adjusting for confounders and creatinine standardization, urinary concentrations of iodine [odds ratio (OR) = 11.01, 95% confidence interval (CI): 1.97–30.52] and perchlorate (OR = 2.27, 95% CI: 1.03–5.03) were associated with the risk of PTC, whereas urinary thiocyanate concentration showed a negative association (OR = 0.24, 95% CI: 0.09–0.65). Conclusions: Increased exposure to iodine and perchlorate may affect PTC development, whereas high thiocyanate exposure may have a beneficial effect. Highlights: We evaluate the association of urinary iodine, perchlorate and thiocyanate with PTC risk. Urinary iodine and perchlorate levels were significantly associated with PTC risk. Urinary thiocyanate concentration showed a negative effect.